Work From Home dan Beban Kerja Terhadap Kinerja Pegawai dengan Kepuasan Kerja sebagai Variabel Intervening - Annisa Nurhandayani (Journal of Management and Bussines (JOMB), 2023)
This study aims to determine and analyze the effect of Work from Home and workload on employee performance through job satisfaction as an intervening variable. This research method is quantitative. The sampling method used in this study uses non-probability sampling. The data analysis technique used is the inner model with the bootstrapping method. The data that has been obtained is processed using SmartPLS 3.0. The results showed, a) the Work from Home variable on employee performance showed an estimated value of 0.111 and a t-statistic value of 1.389<1.96, with a p-value of 0.165>0.5; b) the workload variable on employee performance shows an estimated value of 0.419 and a t-statistic value of 4.526> 1.96, with a p-value of 0.000 <0.05; c) the Work from Home variable on job satisfaction shows an estimated value of 0.389 and a t-statistic value of 3.161> 1.96, with a p-value of 0.002 <0.05; d) the workload variable on job satisfaction shows an estimated value of 0.193 and a t-statistic value of 1.748<1.96, with a p-value of 0.081>0.05; e) the variable of job satisfaction on employee performance shows an estimated value of 0.395 and a t-statistic value of 4.637> 1.96, with a p-value of 0.000 <0.05. In conclusion, Work from Home has effect on employee performance, workload has a negative effect on employee performance. Work from Home has a positive effect on job satisfaction. Workload has no effect on job satisfaction. Job satisfaction has a positive effect on employee performance. Keywords: Workload, Job Satisfaction, Employee Performance, Work from Home